First report of Tuta absoluta Meyrick (Lepidoptera: Gelechiidae) in the Republic of Benin - Karlsson, M.F.; Sikirou, R.; Mama, S.S.; Zannou, J.A.; Georgen, G. (Regional Euro-Asian Biological Invasions Centre Oy (REABIC), 2018)
Tomato leafminer Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) is a serious pest of tomato Solanum lycopersicum L. (Solanaceae) originating from South America. Due to previous outbreaks in neighbouring West African countries, surveillance was ongoing since 2014 in Benin. Tomato plants were regularly inspected and pheromone traps placed in tomato-producing localities in northern, southern and central Benin, including fields close to the border with Niger and Nigeria. In late 2017 and beginning of 2018 Gelechiidae moths were obtained from both the traps and the reared plant material. Morphological examination and molecular analysis of the gained specimens allowed to confirm the presence of the pest in the northern and central regions of Benin. We hence confirm the presence of T. absoluta in yet another West African country.